2001
DOI: 10.1016/s0735-1097(00)01052-4
|View full text |Cite|
|
Sign up to set email alerts
|

Argentine randomized study: coronary angioplasty with stenting versus coronary bypass surgery in patients with multiple-vessel disease (ERACI II): 30-day and one-year follow-up results

Abstract: In this selected high-risk group of patients with multivessel disease, PTCR with stent implantation showed better survival and freedom from MI than did conventional surgery. Repeat revascularization procedures were higher in the PTCR group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
145
4
12

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(172 citation statements)
references
References 31 publications
11
145
4
12
Order By: Relevance
“…[99][100][101][102][103][104] Two other trials met the inclusion criteria. One 105 aimed to randomise 280 patients and was completed.…”
Section: Cabg: Included Studies Introductionmentioning
confidence: 99%
“…[99][100][101][102][103][104] Two other trials met the inclusion criteria. One 105 aimed to randomise 280 patients and was completed.…”
Section: Cabg: Included Studies Introductionmentioning
confidence: 99%
“…Over the two last decades, several works have demonstrated that PTA has similar results to CABG in respect to mortality, acute myocardial infarction and strokes. But, independently of the use of balloons, CIS and, over the last years, DCIS, the number of re-interventions has been the greatest obstacle of the PTA procedure [15][16][17]. Another point considered has been the cost of these procedures [18], which has been unfavorable in respect to the CABG over the first years [19], with the exception of some groups [17,20,21].…”
Section: Resultsmentioning
confidence: 99%
“…Deste modo, os estudos ARTS e ERACI II foram realizados para avaliar esta questão, utilizando stents de segunda e terceira geração, assim como protocolo farmacológico anti-agregante plaquetário atual. Essas investigações confirmaram os bons resultados iniciais que o implante de stents havia apresentado em multiarteriais, ou seja, mortalidade de 2,5 e 3,1% em 12 e 20 meses, respectivamente, e necessidade de revascularização adicional de 16,8% em ambos os estudos 5,27 . O estudo ARTS também evidenciou uma taxa de eventos cardiovasculares adversos maiores de 26,2% e ao se comparar os resultados do implante de stents com os da revascularização cirúrgica, verificaram-se resultados similares em relação aos principais eventos clínicos irreversíveis (óbito, acidente vascular encefálico e infarto agudo do miocárdio).…”
Section: Tabela VII -Resultados Do Estudo Arts Em 12 Mesesunclassified
“…Já a análise 18,5±6,4 meses mostrou melhores resultados de sobrevida e IAM-Q no grupo angioplastia transluminal coronária, entretanto esse grupo apresentou taxa de angina recorrente mais elevada e maior necessidade de procedimentos adicionais de revascularização. Quanto aos custos, as duas técnicas mostraram-se similares na Argentina em 20 meses de evolução [25][26][27] (tab. VI).…”
Section: Estudo Eraci II ( Argentine Randomized Study Coronary Angiopunclassified